INFORMAL ECONOMY IN BOSNIA AND HERZEGOVINA - AN EMPIRICAL INVESTIGATION (The South East European Journal of Economics and Business, 2018)
This paper explores the size of informal economy in Bosnia and Herzegovina (BiH) over the period 1998-2016, based on an indirect method of measurement known as MIMIC approach (Multiple Input Multiple Causes). As the underlying determinants of informal economy in BiH we include tax burden, the level of unemployment, the size of agricultural sector and the level of government subsidies. We estimate that the average informal economy for the observed period was 34% of GDP, being the largest in 1998 (43%) and the smallest in 2009 and 2016 (30%). There is a modest decreasing trend of the size of informal economy over time. Our model identifies two structural brakes over the observed period; the first positive one is linked to the introduction of the value added tax in 2006 (a decrease in 2007-2009 follows) and, the second one captures a short-run negative effect of the latest global economic crisis in 2009 (an increase 2010-2011). To further asses these results and check their consistency with available primary data, we investigate the size of the undeclared work, assess tax morality and additional income of families coming from informal sector; these indicators provide consistent results with the MIMIC outcomes.